2017
DOI: 10.1002/pssb.201600634
|View full text |Cite
|
Sign up to set email alerts
|

Elastic and thermodynamic properties of the Ti2AlNb orthorhombic phase from first‐principles calculations

Abstract: Ti2AlNb‐based alloy with a dominated orthorhombic phase is one of the most promising high‐temperature structural materials. In this work, the equilibrium volume, elastic, and thermodynamic properties of the ordered O phase with stoichiometric Ti2AlNb were predicted under different temperatures using first‐principles calculations based on density functional theory combined with quasi‐harmonic approximation (QHA). With the increase of temperature from 0 to 1300 K, the elastic properties decrease moderately and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…31 (The PBE functional has been proven to be more accurate in first-principles calculation studies of Ti 2 AlNb and γ-TiAl systems as shown in ref. 24, 32 and 33.) Projector augmented wave (PAW) pseudopotentials are used in the present study.…”
Section: Computational Detailsmentioning
confidence: 99%
“…31 (The PBE functional has been proven to be more accurate in first-principles calculation studies of Ti 2 AlNb and γ-TiAl systems as shown in ref. 24, 32 and 33.) Projector augmented wave (PAW) pseudopotentials are used in the present study.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The O phase possesses improved ductility when compared to the α 2 phase since the <2c+a> slip system can be activated due to the low critical shear stress for slip activation [37,44]. The elasticity moduli of O, B2, α 2 and (Ti, Nb)B are 148.0 [45], 132.2 [30], 151.7 [46,47] and 453 GPa [30], respectively. The stiffness of the PPBs area, which is full of α 2 and (Ti, Nb)B phases, is higher than the matrix area, resulting in the stress concentration of the PPBs area during the tensile process.…”
Section: α2-precipitated Amountmentioning
confidence: 99%
“…Although the ground-state elastic properties of some constituent phases in high-Nb containing TiAl alloys have already been investigated in both theory and experiment [13,14,15,16,17,18,19,20,21,22], the elastic properties of various phases under pressure have rarely been studied. Up to now, the structural and elastic properties of γ-TiAl, α2-Ti3Al and B19-TiAl phases under pressure have been investigated by using first-principles calculations [23,24,25,26].…”
Section: Introductionmentioning
confidence: 99%